2019
DOI: 10.1016/j.seppur.2019.01.050
|View full text |Cite
|
Sign up to set email alerts
|

A pilot scale study on the concentration of milk and whey by forward osmosis

Abstract: The concentration of skim milk and whey was investigated at a pilot scale using forward osmosis membranes with an installed membrane area of 24 m 2 . The pilot plant was operated in batch mode using a draw solution (48-57 g/L of NaCl) that mimics the potential brine streams available in a dairy processing plant. This approach avoids or limits the need for the regeneration of a synthetic draw solution. A concentration factor of ~2.5 was achieved for both the skim milk and fresh whey, resulting in a total solids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 28 publications
0
28
0
2
Order By: Relevance
“…Pressure-less operation results in a unique process with a low fouling propensity [1], a high rejection of solutes [2], and low energy consumption [3]. Osmotically driven membrane processes have been intensively studied for decades in academia, but it was not until recently that progress in commercialization of this technology has manifested through multiple industrial applications of commercial FO membranes in pilot and full-scale installations (e.g., [4,5,6,7,8,9]). Due to the relatively early stage of this technology’s development, FO membranes with diverse form factors can be found on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure-less operation results in a unique process with a low fouling propensity [1], a high rejection of solutes [2], and low energy consumption [3]. Osmotically driven membrane processes have been intensively studied for decades in academia, but it was not until recently that progress in commercialization of this technology has manifested through multiple industrial applications of commercial FO membranes in pilot and full-scale installations (e.g., [4,5,6,7,8,9]). Due to the relatively early stage of this technology’s development, FO membranes with diverse form factors can be found on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Only one FO study dedicated to skim milk concentration was reported. In that study performed on an 8´´ pilot scale setup, the concentration objective of 2.5 fold was achieved (from 8 to 21% wt) [ 62 ], proving the feasibility to concentrate milk using FO. The passage of small organic molecules was detected, which caused foaming in the draw solution during the concentration process.…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…Wang et al, using in-house made TFC HF membranes, also reached 22% dry solids whey thanks to a CF of 3.6 [ 66 ]. Chen et al evaluated whey concentration potential by FO, reaching a CF of 2.5 times and without significant change in dry product composition [ 62 ]. This study also pointed out that significant energy savings can be achieved using FO instead of thermal processes or (standalone) RO.…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…Worldwide, more than 300,000 m 2 are installed for food processing, and of that 40% is used in dairy [51]. Among others, the following applications have been reported [114], here arranged based on pore size of the membrane: Lately, also forward osmosis [21,148] and thermo-dialysis [46,47] have been suggested for concentration purposes of dairy stream such as milk and whey, leading to water removal at low energy input. For more information on water treatment by reverse osmosis, which is also very important for food production, the interested reader is referred through to a recent review [5].…”
Section: Membranes In Food Processingmentioning
confidence: 99%